Strategi Meningkatkan Literasi Mahasiswa STIT Madani Yogyakarta Berbasis Google Scholar - Muhammad Thaariq; Adi Haironi (Pusat Riset dan Inovasi Nasional, 2024)
During the 21st century, technology has had a positive impact on education, both formal and non-formal, by facilitating access to information and making learning more interactive. One significant impact is on literacy, which now includes the ability to read, write, access, understand, evaluate, and use digital information, including through Google Scholar. Launched in 2004, Google Scholar makes it easy to find high-quality academic literature. This research aims to improve the literacy of STIT Madani Yogyakarta students using Google Scholar. The library method was used to collect related reading materials, with 9 selected articles as references. The strategies identified include: creating an organizational structure for clear guidelines and responsibilities, providing free internet on campus, and digital literacy socialization and training. This strategy is expected to improve students' digital literacy, facilitate access to academic resources, and develop the skills necessary for success in academic and professional environments.